2012
DOI: 10.1111/j.1601-0825.2011.01898.x
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular and dental manifestations of Gaucher disease

Abstract: Gaucher disease is a systemic lysosomal storage disorder with a high prevalence among Ashkenazi Jews. It is caused by an inherited deficiency of the lysosomal enzyme glucocerebrosidase. Common signs and symptoms include hepatosplenomegaly, anemia, thrombocytopenia, and skeletal involvement. Oral and dental manifestations are less commonly seen. These manifestations are often asymptomatic, although they may be detected by routine dental x-rays. There are several case reports and a few larger series published de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 55 publications
1
37
0
1
Order By: Relevance
“…27 Given that jaw involvement in Gaucher is asymptomatic, no treatment is indicated and a follow-up is sufficient. 17 As previously mentioned, partial reversal of mandibular changes may be achieved by enzyme replacement therapy. 27 However, Hall et al reported complete healing after debridement of a Gaucher defect in the mandible, which was stable at a 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…27 Given that jaw involvement in Gaucher is asymptomatic, no treatment is indicated and a follow-up is sufficient. 17 As previously mentioned, partial reversal of mandibular changes may be achieved by enzyme replacement therapy. 27 However, Hall et al reported complete healing after debridement of a Gaucher defect in the mandible, which was stable at a 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…41 Recently, Saranjam et al comprehensively reviewed Gaucher manifestations in the mandible and dental tissue. 17 According to these authors, the most common radiographic observation in an affected mandible is the presence of "pseudocystic" or honeycombed radiolucent lesions, and the cortical bone remains intact. However, the present review refutes these 2 conventions; according to our results, 1) the most prevalent manifestation in the jaws is generalized osteopenia (and the resulting effacement/displacement of the mandibular canal), whereas the well-defined radiolucent lesion is the next most prevalent phenomenon; and 2) cortical bone thinning and perforations, as well as lamina dura thinning, are not uncommon in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The oral manifestations of Gaucher disease (GD) are often detected during routine dental radiographic examinations. 32 These include loss of alveolar bone trabecular architecture, widening of bone marrow spaces, and presence of honeycomb-shaped radiolucent lesions, mainly in the premolar and molar regions. A few studies have reported periodontitis affecting individuals with GD.…”
Section: 4 | Metabolic and Endocrine Disorders (Table 4)mentioning
confidence: 99%